(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of this research is to guide the students when it comes to safety guidelines in terms of wearing face masks, social distancing, and bringing their own hand sanitizer. From the results of the study, respondents assessed the safety protocols has effective when it comes to wearing face masks, social distancing, and bringing their own hand sanitizer. This research found that problems were encountered in face-to-face classes rather than virtual classes. Thus, this research recommended that there should be guidelines to follow within the school premises to lessen the spread of the viruses, especially to students with health probleMs. In conclusion, safety guidelines must be followed for the students’ safety.